O SINCRONISMO DAS AÇÕES VASCULARES DE ESTRÓGENOS EM ESTUDOS EXPERIMENTAIS E HUMANOS - Pereira, Roberta Lélis Dias; Otero, Juliana; Viecili, Paulo Ricardo Nazário; Klafke, Jonatas Zeni (Salão do Conhecimento, 2014)
Resumo